Interfaces between vaccination coverage and Primary Health Care: a retrospective analysis of the last decade in Rondônia (Research, Society and Development, 2023)
Objective: To analyze the infant and adult vaccination coverage, of all immunizers available by PNI, in the state of Rondônia in the last decade. Methodology: Epidemiological, descriptive and quantitative study conducted through the data available in the Information System of Aggressions and Notification - SINAN, of the Information System of the National Immunization Program (SI-PNI) between the years 2013 and 2022. Results: The vaccination coverage (CV) in the state of Rondônia analyzed throughout this historical series is at 80% and, evidences that, despite the efforts and goals stipulated by PNI, there is still low vaccination coverage in some immunizers, among them, double adult and triple acellular in pregnant women (43.57%), DTP (diphtheria, tetanus and pertussis) reinforcement in children aged 4 and 6 years (44.50%), and dTpa in pregnant women (49.52%). The CV was considered expressive, reaching ≥ 95%, the goal recommended by the MS, especially in the first dose of MMR (103.85%) and DTP (102.87%), other immunizers were between or close to the margin established by the Brazilian Society of Immunization. Final Considerations: several factors are related to low CV in the state of Rondônia, among them, socioeconomic vulnerability, access and precariousness of PHC services. In this sense, it is necessary to expand vaccination coverage, strengthen the PNI, access and integrality of care recommended by SUS and pillars of the Family Health Strategy.